A unique SNARE machinery for exocytosis of cytotoxic granules and platelets granules. (19th May 2015) - Tang, Bor Luen
Abstract: Cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells target infected or transformed cells with perforin-containing cytotoxic granules through immune synapses, while platelets secrete several types of granules which contents are essential for thrombosis and hemostasis. Recent work has culminated in the notion that an exocytic SNARE complex, based on a very similar set of components, is primarily responsible for exocytosis of the diverse granules in these different cell types. Granule exocytosis is, in particular, uniquely dependent on the atypical Q-SNARE syntaxin 11, its interacting partners of the Sec/Munc (SM) family, and is regulated by Rab27a. Mutations in these exocytic components underlie disease manifestations of familial hemophagocytic lymphohistiocytosis (FHL) subtypes, characterized by hyperactivation of the immune system, as well as platelet granule secretion defects. Here we discuss the key discoveries that led to the converging notion of the syntaxin 11-based exocytosis machinery for cytotoxic granules and platelet-derived granules.